Management and health of three corn farming systems in the region of Llanos de San Juan, Puebla, Mexico. Issue 1 (2nd January 2017) - Hernández, Edilberto; Pérez, Yolanda del Carmen; Jiménez-García, Daniel; Patrón, José Cinco; Bernal, Héctor
ABSTRACT: In this study, the effects of rainfed maize crop management on agroecosystem health was studied. In the state of Puebla, three systems were analyzed: traditional agriculture (TA), conservation agriculture (CA), and conventional agriculture (CVA). A methodological proposal for evaluation was developed through the Agroecosystem Health Index on an interval scale (0–5), to which a cluster analysis and an ordinal scale (1–3) were applied. Finally, the variance of the data was analyzed under a bifactor design (management, site). The variables of study were chemical, physical, and biological properties of the soil, as well as annual net income of the production unit. The interval scale applied to the chemical properties of the soil indicates that TA has better conditions for growing corn, with a score of 3.6, followed by CA with 3.5, and CVA with 3.3. The cluster analysis only showed correlation with the order of the scores for the type of management. The ordinal scale showed a holistic view of the conditions of the plot's resources and CA was ranked first, followed by CVA and TA, for their ability to promote the health of the agroecosystem. A statistically significant effect of the management was found in all chemical and physical soil properties, whereas for the biological factors it was necessary to analyze the dominant taxonomic groups.